Perioperative urinary thromboxane metabolites and outcome of coronary artery bypass grafting: a nested case-control study. Issue 8 (30th August 2018) - Liu, Hanning; Xu, Zhengxi; Sun, Cheng; Chen, Qianlong; Bao, Ning; Chen, Wen; Zhou, Zhou; Wang, Xiaoqi; Zheng, Zhe
Abstract : Objective: As a marker of in vivo thromboxane generation, high-level urinary thromboxane metabolites (TXA-M) increase the occurrence of cardiovascular events in high-risk patients. To investigate whether perioperative urinary TXA-M level is associated with major adverse cardiac and cerebrovascular events (MACCE) after coronary artery bypass graft (CABG) surgery, we designed a nested case-control study. Design: Observational, nested case-control study. Setting: Single-centre outcomes research in Fuwai Hospital, Beijing, China. Participants: One thousand six hundred and seventy Chinese patients undergoing CABG surgery from September 2011 to October 2013. Methods: We obtained urinary samples from 1670 Chinese patients undergoing CABG 1 hour before surgery (pre-CABG), and 6 hours (post-CABG 6 hours) and 24 hours after surgery (post-CABG 24 hours). Patients were followed up for 1 year, and we observed 56 patients had MACCE. For each patient with MACCE, we matched three control subjects. Perioperative urinary TXA-M of the three time spots was detected in these 224 patients. Results: Post-CABG 24 hours TXA-M is significantly higher than that of patients without MACCE (11 101vs8849 pg/mg creatine, P=0.007). In addition, patients in the intermediate tertile and upper tertile of post-CABG 24 hours urinary TXA-M have a 2.2 times higher (HR 2.22, 95% CI 1.04 to 4.71, P=0.038) and a 2.8 times higher (HR 2.81, 95% CI 1.35 to 5.85, P=0.006) risk of 1 year MACCE than those in the lower tertile, respectively. Conclusions: In conclusion, post-CABG 24 hours urinary TXA-M elevation is associated with an increase of 1 year adverse events after CABG, indicating that the induction of cyclo-oxygenase-2 by surgery-related inflammatory stimuli or platelet turnover may be responsible for the high levels of post-CABG urinary TXA-M. Trial registration number: NCT01573143.